Sustainable Interdependent Networks From Theory to Application - Amini, M. Hadi.; Boroojeni, Kianoosh G.; Iyengar, S.S.; Pardalos, Panos M.; Blaabjerg, Frede; Madni, Asad M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book focuses on the theory and application of interdependent networks. The contributors consider the influential networks including power and energy networks, transportation networks, and social networks. The first part of the book provides the next generation sustainability framework as well as a comprehensive introduction of smart cities with special emphasis on energy, communication, data analytics and transportation. The second part offers solutions to performance and security challenges of developing interdependent networks in terms of networked control systems, scalable computation platforms, and dynamic social networks. The third part examines the role of electric vehicles in the future of sustainable interdependent networks. The fourth and last part of this volume addresses the promises of control and management techniques for the future power grids. Specifies the importance and position of the interdependent networks in the context of developing the sustainable smart cities and power networks; Provides a comprehensive investigation of recently developed optimization methods for large-scale networks, e.g., power systems, social networks, and intelligent transportation networks; Present examples of sustainable campus development, electrified transportation networks, and smart cities.
A Panorama of Future Interdependent Networks: From Intelligent Infrastructures to Smart Cities -- Part 1. Strategic Planning of Developing Sustainable Interdependent Networks -- Calling For a Next Generation Sustainability Framework at MIT -- Towards A Smart City of Interdependent Critical Infrastructure Networks -- Interdependent Interaction of Occupational Burnout and Organizational Commitments: Case Study of Academic Institutions Located In Guangxi Province, China -- Part 2. Solutions to Performance and Security Challenges of Developing Interdependent Networks -- High Performance and Scalable Graph Computation on GPUs -- Security Challenges of Networked Control Systems -- Detecting Community Structure in Dynamic Social Networks Using the Concept of Leadership -- Part 3. Electric Vehicle: A Game-Changing Technology for Future of Interdependent Networks -- Barriers Towards Widespread Adoption Of V2G Technology in Smart Grid Environment: From Labs to Commercialization -- Plug-In Electric VehicleCharging Optimization Using Bio-Inspired Computational Intelligence Methods -- Part 4. Promises of Power Grids for Sustainable Interdependent Networks -- Coordinated Management of Residential Loads in Large Scale Systems -- Estimation of Large-Scale Solar Rooftop PV Potential For Smart Grid Integration: A Methodological Review -- Optimal SVC Allocation in Power Systems for Loss Minimization and Voltage Deviation Reduction -- Decentralized Control of DR using a Multi-Agent Method -- Complex distribution networks: Case Study Galapagos Islands.
Keywords: Telecommunication; Computational intelligence; Data protection; Application software; Energy policy; Energy and state; Water; Hydrology; Communications Engineering, Networks; Computational Intelligence; Data and Information Security; Computer and Information Systems Applications; Energy Policy, Economics and Management; Water